2012
DOI: 10.1007/s10620-012-2290-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Infusion of Bone Marrow-Derived Mesenchymal Stem Cells for Treatment of Experimental Colitis in Mice

Abstract: Systemic infusion of bone marrow-derived MSCs may exert therapeutic efficacy on acute DSS-induced colitis in mice through their anti-inflammatory effects, which demonstrates the feasibility of using bone marrow-derived MSCs to treat IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 33 publications
4
72
2
2
Order By: Relevance
“…Other authors did use MSCs alone to treat IBD. However, although one report claimed that multiple MSC infusion improved the clinical symptoms of IBD, the levels of only TNF-α and IL-1β were shown [10] . Some clinical studies have explored the effects of adipose-derived stem cells (ASCs) and MSCs in IBD patients (Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other authors did use MSCs alone to treat IBD. However, although one report claimed that multiple MSC infusion improved the clinical symptoms of IBD, the levels of only TNF-α and IL-1β were shown [10] . Some clinical studies have explored the effects of adipose-derived stem cells (ASCs) and MSCs in IBD patients (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…However, some authors did not use MSCs alone, rather subjecting the MSCs to IL-12p40 transduction [11] , autoimmune regulator knockout [10] , or coating with antibodies against MAdCAM-1 and VCAM-1 [9] . Other authors did use MSCs alone to treat IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the success of this method in fistulising CD, alternative administration routes that facilitate homing to multiple inflammatory sites may be required to treat pathological manifestations of IBD in its entirety. Systemic administration of MSCs was used in clinical trials treating luminal CD 32,33) and is predominant in studies of experimental colitis ( 34,35) however other studies have not observed this phenomenon [36][37][38] . Additionally, it is likely that MSCs can become sequestered in other various tissues connected to the circulatory system when systemically injected 39) .…”
Section: Route Of Msc Administrationmentioning
confidence: 99%
“…Ha habido algunos estudios donde se utilizaban ratones con enfermedad inflamatoria intestinal inducida que han sido tratados con MSCs, demostrando la viabilidad de esta aplicación (19) (20). En otro artículo, se expone el caso de cuatro pacientes con colitis ulcerosa y leucemia que tras ser tratados con ASCT permanecieron en remisión de ambas patologías (21).…”
Section: Colitis Ulcerosaunclassified